PENGARUH IMPLEMENTASI IFRS S2 DAN PERCEIVED STAKEHOLDER PRESSURE TERHADAP NILAI PERUSAHAAN - Swee Hin (Jurnal Akuntansi, 2026)
This study aims to analyze the influence of IFRS S2 implementation and perceived stakeholder pressure on firm value, focusing on companies in the energy, chemical, construction materials, and plantation sectors listed on the Indonesia Stock Exchange (IDX) in 2024. IFRS S2 is a climate disclosure standard issued by the International Sustainability Standards Board intended to enhance the transparency of climate-related risks and opportunities. Meanwhile, perceived stakeholder pressure refers to management’s perception of external pressure from stakeholders, such as investors, regulators, customers, and the public, in encouraging corporate sustainability practices. This research employs a quantitative approach using secondary data collected from corporate annual and sustainability reports. The IFRS S2 implementation was assessed using 42 disclosure indicators grouped into four major dimensions. Meanwhile, pressure from stakeholders is measured through seven indicators that reveal the existence of external pressure. Firm value was measured using Tobin’s Q ratio. The findings reveal that both IFRS S2 implementation and perceived stakeholder pressure have a positive and significant impact on firm value, both individually and jointly. These results underscore the importance of climate-related disclosure and corporate responsiveness to stakeholder expectations in driving sustainable firm value. This study contributes to the existing literature on climate reporting and sustainability governance and offers practical implications for corporate managers and regulators.